CHARACTERIZATION IN THE NOVEL ENTITLED SONS AND LOVERS BY DH LAWRENCE - La Muhiddin (LINGUA : Jurnal Bahasa, Sastra, dan Pengajarannya, 2015)
This study is qualitative designed to analyze the character of the novel through psychological approach.  The subject of the study is the works of D.H. Lawrence, focusing on the novel "Sons and Lovers". Two kinds of corpuses for analysis were literary elements corpuses, plot, theme, setting and atmosphere, point of view and the main characters corpuses of Gertrude Morel, Walter Morel, William Morel & Miriam Leiver. Data were collected from literary research and library research. The study revealed that the main characters of sons and lovers are round ones. Miriam was said to be very religious, yet she had sexual intercourse before her marriage. It is shown that there are some aspects of moral quality. Educational value appeared in nuance that  revenge does not give us satisfaction. Through out the novel, relevant implication appeared that sexual desire does not belong to love. Sex is also physiological needs and sometimes an expression of love. The self‑actualization need is dominant in Paul.